Sasca A.E.-1 (sasca aeroflare-1) / Danial Haziq Abdul Rahman - Abdul Rahman, Danial Haziq (College of Creative Arts, Universiti Teknologi MARA, Kedah, 2024)
SASCA A.E.-1 (SASCA AEROFLARE-1) is a high-tech concept motorcycle that has intelligent features and modern design elements. The word SASCA, which derives from safety, ability, stability, comfort, and accomplishment, describes a generation of this motorcycle design. The design of this motorcycle is inspired by muscular shapes to give it a bold and powerful appearance. Features of this motorcycle are a full electric powertrain, a hubless wheel, and plenty of storage to provide more space for riders. This motorcycle also adds an intelligent feature such as a keyless sensor that can be easily accessed by the rider, which enhances the safety of this motorcycle, and a helmet detection system to ensure riders always wear a helmet before riding on this motorcycle.